INTRASCLERO-SUPRACILIAR IMPLANTATION OF AMNION WITH NEUROPROTECTIVE PURPOSE AT ADRENALINE INDUCED GLAUCOMA - Malova, N.G.; Demin, J.A.; Kаzmіruk I.L. (World of Medicine and Biology, 2013)
In an experiment on the model of adrenaline induced glaucoma therapeutic efficiency of cryopreserved amnionic shell is studied. Well-proven therapeutic effect of cryopreserved preparation from a амніотичної shell which was expressed by the decline of edema and diminishing of destructive and used for setting fire displays in a retina and visual nerve.